2010
DOI: 10.1038/npp.2010.121
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Dopamine: Unifying Affective, Activational, and Decision Functions

Abstract: Serotonin, like dopamine (DA), has long been implicated in adaptive behavior, including decision making and reinforcement learning. However, although the two neuromodulators are tightly related and have a similar degree of functional importance, compared with DA, we have a much less specific understanding about the mechanisms by which serotonin affects behavior. Here, we draw on recent work on computational models of dopaminergic function to suggest a framework by which many of the seemingly diverse functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
381
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(413 citation statements)
references
References 168 publications
(163 reference statements)
32
381
0
Order By: Relevance
“…Serotonin has been associated with both punishment (12) and behavioral inhibition (13,14,17). One previous study found that tryptophan depletion abolishes punishment-induced inhibition akin to the disadvantage of performing a go response in the avoid losing condition compared with the winning condition we observe in our task (15).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Serotonin has been associated with both punishment (12) and behavioral inhibition (13,14,17). One previous study found that tryptophan depletion abolishes punishment-induced inhibition akin to the disadvantage of performing a go response in the avoid losing condition compared with the winning condition we observe in our task (15).…”
Section: Discussionsupporting
confidence: 47%
“…That is, although the nature of any opponency between appetitive and aversive systems remains the subject of much debate (12)(13)(14), there are suggestions that serotonin acts as a mirror to dopamine and is associated with behavioral inhibition in aversive contexts (13)(14)(15)(16)(17). These joint roles would lead to conflict when punishment can be avoided only by acting (go).…”
mentioning
confidence: 99%
“…Future studies can build on this study work by comparing the effects of MPH with the effects of atomoxetine (a prefrontal specific catecholamine agonist) and observe interactions with specific dopamine and noradrenaline antagonists to isolate the neural structures and specific neurotransmitters involved. Given the distribution of cortical and striatal systems involved in social conformity (Berns et al, 2010;Campbell-Meiklejohn et al, 2010;Klucharev et al, 2009), we expect that, as for nonsocial learning (Kehagia et al, 2010), conformity involves a network of brain regions, multiple cognitions, and interactions between multiple neurotransmitter systems (Boureau and Dayan, 2011;Cools et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, both increasing and decreasing effects of serotonin on reward have been reported (Kranz et al, 2010) and, in contrast to dopamine, serotonin does not appear to be critically involved in hippocampal memory formation (Thomas, 2015;Werlen and Jones, 2015). Several theories proposed that serotonin signals "punishment prediction error" as an opponent to dopamine (Cools et al, 2011;Doya, 2002), however recent evidence does not support this proposal. A study in behaving monkeys (Bromberg-Martin et al, 2010a) showed that in contrast to dopaminergic neurons in the SN, dorsal raphe-nucleus neurons' activity is modulated before and after reward delivery by expected and received reward values.…”
Section: Box 2: Role Of Sleep In the Consolidation And Generalizationmentioning
confidence: 98%